Flexible work and free time: Postmodern utopias (Research, Society and Development, 2021)
The transformations in the world of work in the late 1990s and the first decades of the 21st century substantially altered the spatio-temporal relations and workers' productivity. New arrangements due to the informational and specialized nature of home office services have fostered the social belief that we are in the era of flexible work and free time. In this sense, the aim of this essay is to demonstrate that free time in Marx's perspective, possible only with the reduction of working hours, in post-modernity takes on a utopian guise in which, increasingly, the worker has been transforming the reserved period to rest in other forms of work such as uberization and telework. This study is bibliographic and what was found is that the fetish of flexibility and free time for the worker is one of the great attractions for adherence to types of flexible work, being another strategy of capitalism for the exploitation of labor physical and intellectual of the worker.